2006
DOI: 10.1074/jbc.m603781200
|View full text |Cite
|
Sign up to set email alerts
|

Sterol Intermediates from Cholesterol Biosynthetic Pathway as Liver X Receptor Ligands

Abstract: The liver X receptors (LXRs) are ligand-activated transcription factors that regulate the expression of genes controlling lipid metabolism. Oxysterols bind LXRs with high affinity in vitro and are implicated as ligands for the receptor. We showed previously that accumulation of selected dietary sterols, in particular stigmasterol, is associated with activation of LXR in vivo. In the course of the defining of structural features of stigmasterol that confer LXR agonist activity, we determined that the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
216
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 257 publications
(227 citation statements)
references
References 52 publications
9
216
0
2
Order By: Relevance
“…Thus, its levels could relate either to direct effects of desmosterol or reflect changes in other components of the cholesterol synthesis pathway. Desmosterol strongly activates LXR target genes in vivo 35,36 and in a mouse model deficient for the gene coding the desmosterol reductase enzyme (DHCR24), which catalyzes the conversion of desmosterol into cholesterol. 37,38 Our gene expression results support the view that desmosterol may have a specific role in activating, e.g., LXR target genes, as compared to cholestenol and lathosterol (Supporting Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, its levels could relate either to direct effects of desmosterol or reflect changes in other components of the cholesterol synthesis pathway. Desmosterol strongly activates LXR target genes in vivo 35,36 and in a mouse model deficient for the gene coding the desmosterol reductase enzyme (DHCR24), which catalyzes the conversion of desmosterol into cholesterol. 37,38 Our gene expression results support the view that desmosterol may have a specific role in activating, e.g., LXR target genes, as compared to cholestenol and lathosterol (Supporting Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the infantile consumption of sitosterol is estimated at around 1,000 mg/ day if an infant ingests 1,000 ml of breast milk per day; this amount of sitosterol intake is close to that of an adult but greater in terms of proportion with body weight. The accumulation of non-cholesterol sterols contributes to the very low cholesterol biosynthesis in cases with sitosterolaemia (Yang et al 2006), leading us to speculate that severe hypercholesterolaemia observed in infantile sitosterolaemia during breastfeeding reflects the reduced catabolism of LDL or excretion of cholesterol into the bile, rather than an increase in cholesterol biosynthesis. Compared with the dietary intake of cholesterol by adults, infants ingest about 3 to 4 times the amount of cholesterol per kg body weight through breast milk (Ohta et al 2002;Ohlsson 2010), or the high content of saturated fatty acids in breast milk (Ohlsson 2010), which may explain the extreme hypercholesterolaemia of infants with sitosterolaemia.…”
Section: Discussionmentioning
confidence: 99%
“…36 The natural ligands for LXR include sterols made in the mevalonate pathway, including the oxysterol 24(S),25-epoxycholesterol 37 and the cholesterol biosynthetic precursor desmosterol. 38 Given that APD treatment results in the accumulation of a diverse array of intermediates/products of the mevalonate pathway (Supplementary Figure 5), it is possible that these may include activators of LXR. Alternatively, the APDs may themselves act as LXR agonists.…”
Section: A Panel Of Atypical Apds Inhibit Cholesterol Trafficking To mentioning
confidence: 99%